Early pathologic amyloid induces hypersynchrony of BOLD resting‐state networks in transgenic mice and provides an early therapeutic window before amyloid plaque deposition. Issue 9 (21st April 2016) - Shah, Disha; Praet, Jelle; Latif Hernandez, Amira; Höfling, Corinna; Anckaerts, Cynthia; Bard, Frédérique; Morawski, Markus; Detrez, Jan R.; Prinsen, Els; Villa, Alessandro; De Vos, Winnok H.; Maggi, Adriana; et al.
Abstract: Introduction: In Alzheimer's disease (AD), pathologic amyloid‐beta (Aβ) is synaptotoxic and impairs neuronal function at the microscale, influencing brain networks at the macroscale before Aβ deposition. The latter can be detected noninvasively, in vivo, using resting‐state functional MRI (rsfMRI), a technique used to assess brain functional connectivity (FC). Methods: RsfMRI was performed longitudinally in TG2576 and PDAPP mice, starting before Aβ deposition to determine the earliest FC changes. Additionally, the role of pathologic Aβ on early FC alterations was investigated by treating TG2576 mice with the 3D6 anti‐Aβ‐antibody. Results: Both transgenic models showed hypersynchronized FC before Aβ deposition and hyposynchronized FC at later stages. Early anti‐Aβ treatment in TG2576 mice prevented hypersynchronous FC and the associated synaptic impairments and excitatory/inhibitory disbalances. Discussion: Hypersynchrony of FC may be used as a new noninvasive read out of early AD and can be recovered by anti‐Aβ treatment, encouraging preventive treatment strategies in familial AD.